Treatment Gaps Found in the Management of Type 2 Diabetes at a Community Health Centre in Johannesburg, South Africa - Yacob Pinchevsky; Neil Butkow; Tobias Chirwa; Frederick Raal (Journal of Diabetes Research, 2017)
Aims. The management of cardiometabolic goals or “ABCs” (HbA1c, blood pressure (BP), and cholesterol) ultimately determines the morbidity and mortality outcomes in patients with type 2 diabetes mellitus (T2DM). We sought to determine if patients with T2DM attending an urbanized public sector community health centre (CHC) were having their ABCs measured, were treated with appropriate cardioprotective agents and finally, were achieving guideline-based targets. Methods and Results. A cross-sectional record review of 519 patients was conducted between May and August 2015. The mean age was 54 years (SD: ±11.5) and 54% (n=280) were females. Testing of ABCs occurred in 68.8% (n=357) for HbA1c, 95.4% (n=495) for BP, and 58.6% (n=304) for LDL-C. Achievement of ABC targets was as follows: 19.3% (HbA1c < 7%), 22.0% (BP < 140/80 mmHg), and 56.3% (LDL-C < 2.5 mmol/l). Conclusion. There were a significant number of patients who were not tested nor received adequate pharmacotherapy or achieved their ABC targets. This places these patients at an increased risk for the development of diabetes-related complications. Although the realities of resource constraints exist in South Africa’s public sector settings, a wider implementation of evidence-based guidelines must be instituted in order to ensure better patient outcomes.